Answer :
If [tex]i=\sqrt{-1}[/tex], then [tex]i^2=-1[/tex], [tex]i^3=-i[/tex], and [tex]i^4=1[/tex].
We can break up the given sum into 25 groups (after adding and subtracting [tex]i^{100}[/tex]):
[tex](i+i^2+i^3+i^4)+(i^5+i^6+i^7+i^8)+\cdots+(i^{97}+i^{98}+i^{99}+i^{100})-i^{100}[/tex]
We have
[tex]i+i^2+i^3+i^4=i-1-i+1=0[/tex]
and in each group, we can pull this out as a factor. For example,
[tex]i^{97}+i^{98}+i^{99}+i^{100}=i^{96}(i+i^2+i^3+i^4)=0[/tex]
So the entire sum reduces to the remaining term,
[tex]-i^{100}=-i^{25\cdot4}=-(i^4)^{25}=-1^{25}=\boxed{-1}[/tex]
Answer:
jhjhjhjjjhjhjjjjh and yea that .....................................................................................................................................................................
Step-by-step explanation: